Pinto Centauro, new variety of beans for the State of Durango - Rosales Serna, Rigoberto; Ibarra Pérez Francisco Javier; Cuéllar Robles Evenor Idilio (Revista Mexicana de Ciencias Agrícolas, 2018)
The pinto grains beans are the main commercial class produced by rainfed farmers in Durango. Currently, pinto grains beans varieties are required, tolerant to the darkening of the testa, early grain maturity and larger grains compared to Pinto Saltillo, which is the most popular variety because of its long shelf-life and high prices. The aim was to develop a superior variety of beans than Pinto Saltillo, in earliness, grain size and commercial quality. At INIFAP-Durango was recorded in 2010 Pinto Centauro, with the pedigree method, from the cross between Pinto Mestizo and Pinto Saltillo [(Pinto Mestizo/ Pinto Saltillo)-5-4]. This variety showed an average yield of 1 220 kg ha-1 and fluctuations between 169 kg ha-1 to 2 935 kg ha-1. Pinto Centauro, on average compared to Pinto Saltillo was found with earlier maturity (90 vs. 94. Days) and presented higher grain size, measured by the weight of 100 seeds (34 g vs 31 g). The growth habit of Pinto Centauro is of indeterminate vine with short non-climbing guides, the average canopy height is 32 cm and 68 cm growing guide. Pinto Centauro has 34 g/100 seeds and a weight range from 28 to 42 g/100 seeds. The grain is transversely elliptical, externally kidney-shaped, cream-colored seed coat, rich brown paints and the hilum is yellow. Pinto Centauro showed tolerance to anthracnose and rust, as well as medium and high values of susceptibility to the common blight and root rot. This variety is in the process of diffusion to determine its potential for adoption, adaptability and potential to increasing yield and quality of pinto beans produced in Durango.